Prevalence and Economic Importance of Bovine Hydatidosis in Animal Slaughtered in Dalomana Municipal Abattoir Southeastern, Ethiopia - Sufian Abdo Jilo; Sadik Zakir Abadura; Nigatu Taddese Shibashi; Johar Aliye Hussein; Sureshkumar P.Nair; Aliyi Adem Gelchu (Journal of Veterinary Healthcare, 2022)
A cross-sectional study was conducted on bovine hydatidosis from May 2018 to November 2020 with the aims of finding its incidence and economic losses in bovine slaughtered for human consumption in Dalomana municipality abattoir. Usual ante mortem and post-mortem inspection was carried out on overall of 430 selected slaughtered cattle. From this total inspected, 82(19.1%) of them had harboured hydatid cyst (s) in one or more of their organ’s. Age and body condition as a risk factor were statistically significant as older zebus and medium were more infected (P<0.05, χ2= 14.597 and p value<0.05 χ2=9.68) respectively. Similarly, the geographical origin of the animals had significant contribution on hyadatid cyst distribution (P < 0.05, χ2 =12.724). Sex was statistically non-significant (P>0.05,χ2 =0.74) and have no difference. The single and multiple organs were infected by hydatid cysts. From the total of 282 hydatid cysts collected and characterized lung and livertook more percentage in harboring cysts, from this 137(48.58%) and 126(44.68%) cysts were observed in lung and liver respectively and 19(6.74%) are observed in other organ, such as spleen, kidney, and heart. The study indicated that annual economic failure due to direct organ condemnation and indirect carcass weight loss from the disease in Dalomana was estimated to be 105769.657 ETB. Hence, bovine hydatidosis is significantly a common disease in cattle, with severe public health fears and leads considerable servable and undetectable losses in bovine in Dalomana and its surroundings.
Keywords: Bovine